2015
DOI: 10.15390/eb.2015.4410
|View full text |Cite
|
Sign up to set email alerts
|

Examining Social Anxiety Among Adolescents in Accordance with Coping with Stress Approaches

Abstract: Bu araştırmanın amacı üniversite öğrencilerinin sosyal kaygıları ile stresle başa çıkma stilleri arasında anlamlı düzeyde ilişki olup olmadığını ve stresle başa çıkma tarzlarının sosyal kaygıyı anlamlı düzeyde yordayıp yordamadığını belirlemektir. Araştırma sonucunda sosyal kaygının sosyal kaçınma, değersizlik ve kritize edilme alt boyutları ile stresle başa çıkmanın kendine güvenli yaklaşım ve iyimser yaklaşımlar arasında anlamlı düzeyde negatif ilişki, çaresiz yaklaşım, boyun eğici yaklaşım ve sosyal destek … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…Likewise, Cui et al (2021) discovered that negative coping approaches were significantly associated with Covid-19 anxiety. Hamarta (2015) and Acaroğlu et al ( 2008) also suggested that there was positive association between submissive and helpless approaches and anxiety. Another study (Yıldırım et al, 2021) indicated that positive coping had improving effect on the Covid-19 anxiety.…”
Section: Discussionmentioning
confidence: 95%
“…Likewise, Cui et al (2021) discovered that negative coping approaches were significantly associated with Covid-19 anxiety. Hamarta (2015) and Acaroğlu et al ( 2008) also suggested that there was positive association between submissive and helpless approaches and anxiety. Another study (Yıldırım et al, 2021) indicated that positive coping had improving effect on the Covid-19 anxiety.…”
Section: Discussionmentioning
confidence: 95%